An Assessment of the Psychosocial Evaluation for Early Liver Transplantation in Patients With Acute Alcoholic Hepatitis in the Context of Alcohol Use Disorder, a Case-Control Study. (August 2022) - Dienstag, Aryeh; Dienstag, Penina; Mohan, Kanwal; Mirza, Omar; Schubert, Elizabeth; Ford, Laura; Edelman, Margot; Im, Gene; Shenoy, Akhil
Background: Severe acute alcoholic hepatitis (AAH) has an extremely poor prognosis with a high short term mortality rate. As a result, many centers, including our own, have allowed transplant patients to be listed for transplantation prior to achieving 6-months of sobriety. Several scoring systems, designed to target patients with a minimal period of sobriety, have been proposed to identify patients with alcohol use disorder (AUD), who would be predisposed to relapse after liver transplantation. We investigated whether these scoring systems corroborated the results of the non-structured selection criteria used by our center regarding decision to list for transplant. Methods: We conducted a retrospective case-control study of 11 patients who underwent early liver transplantation for AAH matched with 11 controls who were declined secondary to low insight into AUD. Blinded raters confirmed the severity of the diagnosis of DSM-5 and scored the patients on a variety of structured psychometric scales used to predict alcohol relapse. These included the High Risk for Alcohol Relapse Scale (HRAR), Stanford Integrated Psychosocial Assessment Tool (SIPAT), Alcohol Relapse Risk Assessment (ARRA), Hopkins Psychosocial Scale (HPSS), Michigan Alcoholism Prognosis Score (MAPS), Alcohol Use Disorders Identification Test -Consumption (AUDIT-C), and Sustained Alcohol Use Post-Liver Transplant (SALT) scales. All patients who underwent transplantation were followed for harmful and non-harmful drinking until the end of the study period. Results: The transplant recipients had significantly favorable MAPS, HRAR, SIPAT, ARRA, and HPSS scores with cutoffs that matched their previous research. The SALT and AUDIT-C scores were not predictive of our selection of patients for transplantation. Despite an expedited evaluation and no significant period of sobriety, our case cohort had a 30% relapse to harmful drinking after an average of 6.6 years (5-8.5 years) of follow-up. Discussion: Despite the rapid assessment and the short to no period of sobriety, the patient cohort demonstrated a 30% relapse to harmful drinking, consistent with the 20% to 30% relapse to drinking rate reported after liver transplantation for all forms of alcoholic liver disease. Average scores from MAPS, HRAR, SIPAT, ARRA, and HPSS corroborated our current stratification procedures, with lower mean risk scores found in the transplanted group. Conclusion: Patients with AUD and severe AAH who obtain new insight into their disease and posses other favorable psychosocial factors have low rates of AUD relapse post-liver-transplantation. The psychosocial selection criteria for patients with alcoholic hepatitis in our institution are consistent with 4 of the 5 scoring systems investigated in their prediction of sobriety post-transplant.